The global value of coastal wetlands for storm protection. (September 2021) - Costanza, Robert; Anderson, Sharolyn J.; Sutton, Paul; Mulder, Kenneth; Mulder, Obadiah; Kubiszewski, Ida; Wang, Xuantong; Liu, Xin; Pérez-Maqueo, Octavio; Luisa Martinez, M.; Jarvis, Diane; Dee, Greg
Graphical abstract: The effects of tropical cyclones on damages/GDP and lives lost/population in the swath of a tropical cyclone, as moderated by coastal wetlands. Globally coastal wetlands prevent 447 Billion/yr. of damages and save 4, 620 lives/yr. Highlights: 1st global estimate of the value of coastal wetlands for avoiding all storm damages. Median global storm protection value of 447 Billion/yr. and 4, 620 lives saved/yr. Integrated global databases on storms, damages, deaths, wetlands, GDP, & population. Used Bayesian and OLS statistical techniques to relate damages & deaths to wetlands. Coastal wetlands provide storm protection and many other ecosystem services. Abstract: Coastal wetlands provide a range of valuable ecosystem services, including protecting coastal communities from storms. We estimated for the first time the global value of these storm protection services for all coastal wetlands for both damages avoided and lives saved. We used the historical tracks of 1, 014 tropical cyclones since 1902 that recorded property damage and/or human casualties in 71 countries/regions. We used Bayesian and OLS statistical techniques to relate storm damages and lives lost to: wind speed, storm forward speed, the year of the storm, the volume of ocean water proximal to landfall, and GDP, population, and coastal wetlands in the swath of the storm. Based on current storm probabilities, we estimate the median annual global value of coastal wetlands for storm protection at 447 billion/yr (2015US) (213 - 837 billion/yr, 90% CI) and 4, 620 lives saved per year (3, 320 – 6, 550, 90% CI). The 40 million hectares of coastal wetlands in storm prone areas provided an average of 11, 000/ha/yr in avoided storm damages. The frequency and intensity of tropical cyclones has been increasing in recent decades and is projected to further increase with climate change. Consequently, the already significant benefits from protecting and restoring coastal wetlands will become increasingly important and valuable in the future. These results justify much larger investments in conservation and restoration of coastal wetlands.